Metformin-mediated effects on mesenchymal stem cells and mechanisms: proliferation, differentiation and aging - Liu, Xinjuan; Li, Zekun; Liu, Luyun; Zhang, Ping; Wang, Yue; Ding, Gang (Frontiers in Pharmacology, 2024)
Mesenchymal stem cells (MSCs) are a type of pluripotent adult stem cell with strong self-renewal and multi-differentiation abilities. Their excellent biological traits, minimal immunogenicity, and abundant availability have made them the perfect seed cells for treating a wide range of diseases. After more than 60 years of clinical practice, metformin is currently one of the most commonly used hypoglycaemic drugs for type 2 diabetes in clinical practice. In addition, metformin has shown great potential in the treatment of various systemic diseases except for type 2 diabetes in recent years, and the mechanisms are involved with antioxidant stress, anti-inflammatory, and induced autophagy, etc. This article reviews the effects and the underlying mechanisms of metformin on the biological properties, including proliferation, multi-differentiation, and aging, of MSCs in vitro and in vivo with the aim of providing theoretical support for in-depth scientific research and clinical applications in MSCs-mediated disease treatment. considered as MSCs (Pittenger et al., 1999). MSCs are the most widely used postnatal tissue-specific stem cells used in clinical practice, and transplanting MSCs to replace damaged tissues can restore tissue structure and function (Keshavarz et al., 2023). In addition, MSCs were capable of secreting a large number of cytokines and growth factors, and playing multiple roles in immune regulation. Due to its characteristics of self-renewal, multi-directional differentiation potential, and low immunogenicity, MSCs have been considered as an excellent seed cells for regenerative medicine and tissue engineering and have been used in the research and treatment of various diseases (